Advances, challenges, and directions for ecological restoration by direct seeding of trees: Lessons from Brazil - de Souza, Diego Cerveira [UNESP]; Engel, Vera Lex [UNESP] (Elsevier, 2023)
Direct seeding has been considered a cost-effective system for ecological restoration with tree species, compared to planting nursery-raised seedlings. Over the last years, several field experiments have been conducted in worldwide to enhance the success of the technique and to test its feasibility at different sites, sowing conditions, and species composition. Based on the analysis of data sets from 53 field experiments conducted in Brazil, we (1) assessed the technical and ecological feasibility of direct seeding systems for ecological restoration using tree species, (2) synthesized the main advances and challenges already reported, and (3) provided future guidelines for restoration scientists and practitioners. Our study indicates that direct seeding is mostly conducted in the two Brazilian hotspots (Atlantic Forest and Cerrado), on abandoned pastures, and using a high number of seeds per hectare. Establishment and growth rates are very low for most sites, but survival rates are usually high. To achieve satisfactory tree seedling density and ground coverage, and to eliminate exotic species that constrain natural regeneration and succession, it is necessary to use a high number of viable seeds. Currently, seed stocks are not promptly available to support direct seeding techniques applicability on larger scales. Although direct seeding can be considered a cost-effective system for forest restoration, this technique still needs to be improved before its recommendation on large scale, especially to enhance seedling emergence, establishment, and early growth of tree species, and reduce associated risks.
Keywords: Direct sowing; Ecological restoration; Restoration costs; Seedling establishment; Seeds